Long-term retention and survival of cemented implant-supported zirconia and metal-ceramic single crowns: a retrospective study - Rammelsberg, Peter; Klotz, Anna-Luisa (Clinical oral implants research, 2024)
Objectives To evaluate the effect of different cement types on the incidence of failure and loss of retention of zirconia and metal-ceramic single crowns (SCs) cemented on implant abutments. Methods We placed 567 implant-supported SCs in 358 patients and retrospectively evaluated long-term retention for up to 12.8 years. The frameworks were made from metal alloy (n = 307) or zirconia (n = 260). SCs were cemented with permanent (glass-ionomer cement; n = 376) or semipermanent cement (zinc oxide non-eugenol cement; n = 191) on standardized (n = 446) or customized (n = 121) abutments. Kaplan-Meier curves were used to calculate the incidence of decementation. Differences between survival curves were assessed with log-rank tests. Cox-regression analysis was performed to evaluate multiple risk factors. Results Of the 567 SCs, 22 failed because of technical complications and four because of implant loss. Loss of retention was observed in 50 SCs. Analysis revealed a 7% probability of loss of retention for zirconia and 16% for metal-ceramic SCs after 10 years (p = .011). After 5 years, loss of retention was higher for standardized abutments than for customized abutments (p = .014). The probability of loss of retention was higher with semipermanent than with permanent cement (p = .001). Cox-regression analysis revealed semipermanent cement as the only significant risk factor for SC failure (p = .026). Conclusions In contrast to semipermanent cement, permanent cement provides acceptable long-term retention of cemented implant-supported SCs. These possible positive effects of customized abutments have to be controlled with larger sample sizes.
Veröffentlicht: 02 July 2024
Gesehen am 29.01.2025